2018
DOI: 10.4012/dmj.2016-287
|View full text |Cite
|
Sign up to set email alerts
|

Transmittance of visible and blue light through zirconia

Abstract: The aim of this study was to evaluate the transmittance of visible light (VL) (λ: 400-700 nm) and blue light (BL) (λ: 360-540 nm) through six CAD/CAM zirconia blanks (ZiB) in comparison to a lithium disilicate ceramic (LS2). Disks of the zirconia materials Bruxzir (BX), Cercon (CE), Lava Frame (LF), Lava Plus (LP), Prettau (PT), Zenostar (ZS) and LS2 (EM) were manufactured and the transmittance was measured in a spectrophotometer. ZS, followed by CE, PT, LP, LF, and BX showed the lowest transmittance of VL and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
(48 reference statements)
0
15
0
1
Order By: Relevance
“…It has been reported that lowering the amount of alumina addition from 0.25 to 0.1 or 0.05 wt.% can significantly increase the translucency. Although alumina elimination improves translucency [17], it requires higher sintering temperatures (>1500 °C) in conjunction with a longer dwell time (6 h) which increases significantly the grain size leading sequentially to reduced translucency [18,19]. Another strategy recently developed by Zhang et al [20,21] to synthesize highly-translucent, strong and aging-resistant zirconia is doping with trivalent ions with larger radius compare to Zr 4+ , that segregate at grain boundaries.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…It has been reported that lowering the amount of alumina addition from 0.25 to 0.1 or 0.05 wt.% can significantly increase the translucency. Although alumina elimination improves translucency [17], it requires higher sintering temperatures (>1500 °C) in conjunction with a longer dwell time (6 h) which increases significantly the grain size leading sequentially to reduced translucency [18,19]. Another strategy recently developed by Zhang et al [20,21] to synthesize highly-translucent, strong and aging-resistant zirconia is doping with trivalent ions with larger radius compare to Zr 4+ , that segregate at grain boundaries.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The explanations for this change in properties of the light-cured resin cement under thicker ceramics may be related to the reduction of the light transmitted by the light-curing unit when crossing a 2 mm thick ceramic 22 . According to Liebermann et al 23 (2018), light transmittance is inversely related to the thickness of the ceramic, which will be crossed by the light beam. That is, the thicker the material, the lower the transmittance of that light 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…According to Liebermann et al 23 (2018), light transmittance is inversely related to the thickness of the ceramic, which will be crossed by the light beam. That is, the thicker the material, the lower the transmittance of that light 22,23 . Transmittance can be defined as the amount of light that passes through a material, part of which is reflected or absorbed 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations